2020
DOI: 10.1038/s41598-020-69560-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combining exercise with long-chain polyunsaturated fatty acid supplementation on cognitive function in the elderly: a randomised controlled trial

Abstract: Multifactorial lifestyle intervention is known to be more effective for ameliorating cognitive decline than single factor intervention; however, the effects of combining exercise with long-chain polyunsaturated fatty acids (LCPUFA) on the elderlies' cognitive function remain unclear. We conducted a randomised, single-masked placebo-controlled trial in non-demented elderly Japanese individuals. Participants were randomly allocated to the exercise with LCPUFA, placebo, or no exercise with placebo (control) group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…In both trials, the cognitive function of the participants was considered to be at the same level as that of the general older population, as the average MoCA-J scores obtained at baseline ( Table 1 and Table 3 ) were at about the same level as the average scores previously reported for older community-dwelling Japanese people [ 39 ]. In terms of LCPUFAs, ARA (9.3% in Trial 1, 9.9% in Trial 2), DHA (6.5% in Trial 1, 6.7% in Trial 2), and EPA (1.9% in Trial 1, 2.0% in Trial 2) compositions in plasma phospholipids and dietary ARA (Trial 1: 172 mg/day, Trial 2: 178 mg/day), DHA (Trial 1: 482 mg/day, Trial 2: 498 mg/day), and EPA (Trial 1: 272 mg/day, Trial 2: 285 mg/day) intakes were within the range reported by previous studies on older Japanese people [ 31 , 42 , 43 , 44 , 45 , 46 ]. These results suggest that the participants in both studies corresponded well with the general population of older Japanese.…”
Section: Discussionsupporting
confidence: 81%
“…In both trials, the cognitive function of the participants was considered to be at the same level as that of the general older population, as the average MoCA-J scores obtained at baseline ( Table 1 and Table 3 ) were at about the same level as the average scores previously reported for older community-dwelling Japanese people [ 39 ]. In terms of LCPUFAs, ARA (9.3% in Trial 1, 9.9% in Trial 2), DHA (6.5% in Trial 1, 6.7% in Trial 2), and EPA (1.9% in Trial 1, 2.0% in Trial 2) compositions in plasma phospholipids and dietary ARA (Trial 1: 172 mg/day, Trial 2: 178 mg/day), DHA (Trial 1: 482 mg/day, Trial 2: 498 mg/day), and EPA (Trial 1: 272 mg/day, Trial 2: 285 mg/day) intakes were within the range reported by previous studies on older Japanese people [ 31 , 42 , 43 , 44 , 45 , 46 ]. These results suggest that the participants in both studies corresponded well with the general population of older Japanese.…”
Section: Discussionsupporting
confidence: 81%
“…214 Omega-3 LCPUFA supplementation can improve brain neurocognitive functions, limit neuroinflammation and stress response defects in aged animal models and clinical trials. [215][216][217][218] Meanwhile, peroxide products of LCPUFA, such as A2E, can cause telomere dysfunction and accelerate RPE cell senescence. 219…”
mentioning
confidence: 99%
“…Cognitive measures employed in the trials are presented in Additional file 1 : Table S2. The most frequently employed measurement was the Mini-Mental State Examination (MMSE) for global cognition [ 38 , 39 , 43 , 44 , 46 , 49 , 53 , 56 ], the delayed recall test from Rey Auditory Verbal Learning Test (RAVLT) for episodic memory [ 43 , 46 , 50 , 58 ], verbal fluency test for executive function [ 42 , 43 , 50 53 , 60 ], digit symbol substitution test for processing speed [ 39 , 46 , 53 ], trail making test A (TMT-A) for attention [ 36 , 42 , 50 , 59 , 60 ] and block design test for visuospatial function [ 39 , 50 ].…”
Section: Resultsmentioning
confidence: 99%